Physiological and sanitary quality of safflower seeds stored for different periods - Menegaes, Janine Farias; Russi Nunes, Ubirajara; Antonello Londero Backes, Fernanda Alice; Swarowsky, Alexandre; Fiorin Tasquetto, Tatiana; de Lima Franzen, Felipe (Comunicata Scientiae, 2023)
The safflower (Carthamus tinctorius L.) crop is of agroeconomic interest due to its wide aptitude for uses, from ornamental to oil extraction, with good adaptability to cultivation throughout the country. However, this crop still presents challenges regarding the quality of its seeds, due to the high susceptibility to attack by phytogenes. Thus, the objective of this work was to evaluate the physiological and sanitary quality of safflower seeds submitted to different storage periods. The experiment was conducted in a completely randomized design, 4x7 (lots of seeds grown in the 2017/2018 harvest: sown in winter and spring 2017 and summer and autumn 2018, and seed storage periods: 0; 6; 12; 18; 24; 30 and 36 sequential months counted from the harvest dates), with four replications. The qualities were evaluated by germination, electrical conductivity, dry mass and seedling length, field emergence and health tests. It was observed that the different lots of safflower seeds are sensitive to prolonged storage, with a reduction in the physiological potential, especially in the percentage of germination and seedling emergence. In addition to the increased incidence of harmful phytopathogens on these seeds. Thus, a period of up to 12 months is recommended to obtain the conservation of safflower seeds.